2010
DOI: 10.1371/journal.pone.0010862
|View full text |Cite
|
Sign up to set email alerts
|

Competition of Escherichia coli DNA Polymerases I, II and III with DNA Pol IV in Stressed Cells

Abstract: Escherichia coli has five DNA polymerases, one of which, the low-fidelity Pol IV or DinB, is required for stress-induced mutagenesis in the well-studied Lac frameshift-reversion assay. Although normally present at ∼200 molecules per cell, Pol IV is recruited to acts of DNA double-strand-break repair, and causes mutagenesis, only when at least two cellular stress responses are activated: the SOS DNA-damage response, which upregulates DinB ∼10-fold, and the RpoS-controlled general-stress response, which upregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 67 publications
2
54
1
1
Order By: Relevance
“…In addition, as with F′ Lac + reversion (e.g., ref. 35), Pol II appears to compete with DinB/Pol IV such that Pol II − cells show increased DSB-dependent SIM that is DinB-dependent (Fig. 3B).…”
Section: Rpos Activates Dsb-dependent Mutation In Unstressed Growingmentioning
confidence: 97%
“…In addition, as with F′ Lac + reversion (e.g., ref. 35), Pol II appears to compete with DinB/Pol IV such that Pol II − cells show increased DSB-dependent SIM that is DinB-dependent (Fig. 3B).…”
Section: Rpos Activates Dsb-dependent Mutation In Unstressed Growingmentioning
confidence: 97%
“…25 To gain mechanistic insight into such competition, we modeled SOS-induced conditions in vitro by reconstituting RDR using relative concentrations of these polymerases in stressed cells. We found that pol IV, which is the most abundant polymerase during stress, outcompetes other DNA polymerases at D-loops, including the multi-subunit pol III replisome.…”
Section: Pol IV Preferentially Extends D-loops During Stressmentioning
confidence: 99%
“…The mechanism of RDR in stressed E. coli cells, however, appears to be very different. For example, since genetic studies indicate that competition exists between DNA polymerases at D-loops in growth-limited E. coli, 25 RDR is likely to be non-processive during stress. Thus, this particular mode of replication may not utilize the replicative DnaB helicase.…”
Section: Perspectives On Error-prone Rdrmentioning
confidence: 99%
“…The genetic system is composed of strains with both an antimutator dnaE allele (dnaE915) (21), encoding a variant of the replicative DNA polymerase active subunit, Pol III␣(915), and the wild-type dinB (dinB ϩ ) or the catalytically inactive dinB(D103N) allele. Pol III␣(915) is an antimutator either because it synthesizes DNA slower than the native replicative DNA polymerase active subunit, DNA Pol III␣ (21,22), or because it might inhibit low-fidelity DNA synthesis by TLS DNA polymerases, specifically DinB (23). Its antimutator activity is also dependent upon another TLS DNA polymerase, DNA Pol II, which likely prevents mutagenesis generated by DinB (24).…”
mentioning
confidence: 99%